Reality Counseling to Reduce Students' Cybersex Addiction Behavior: Protocol Guide - Eva Nurul Fajriyah; Aam Imaddudin; Anandha Putri Rahimsyah (Journal of Mental Health and Well-Being in Counseling, 2025)
The turbulent sexual development of adolescents and their high curiosity about sexuality lead some teenagers to choose cybersex to satisfy their sexual desires. Cybersex is a behavior performed for sexual pleasure through media with internet connections stored in gadgets or computers, making it easier for some teenagers to access sexual content. Therefore, guidance and supervision from family, peer groups, schools, and school counselors are needed to provide information and help plan a better self-concept. Cybersex also has three categories: high addiction, moderate addiction, and low addiction. This behavior can result in emotional, social, and addiction-related disturbances that hinder development. Reality counseling is a service focused on current behavior. The WDEP method (Wants, Direction, Evaluation, Plan) helps students understand their behavior, control sexual impulses, and make healthier decisions by emphasizing individual responsibility and focusing on the present condition. It is expected that this service will improve students' self-control and reduce cybersex addiction.